The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2020
DOI: 10.1097/aln.0000000000003236
|View full text |Cite
|
Sign up to set email alerts
|

Volatile Anesthetics versus Propofol for Cardiac Surgery with Cardiopulmonary Bypass

Abstract: Background The aim of this systematic review and meta-analysis was to assess the effect of anesthesia maintenance with volatile agents compared with propofol on both short- and long-term mortality (primary outcomes) and major clinical events in adults undergoing cardiac surgery with cardiopulmonary bypass. Methods Randomized clinical trials on the effects of current volatile anesthetics versus propofol in adults undergoing ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
38
1
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 66 publications
(53 citation statements)
references
References 72 publications
0
38
1
2
Order By: Relevance
“…The authors' analysis of 64 randomized controlled trials (RCTs) demonstrated that one-year mortality was similar between groups 1 . This conclusion stands in stark contrast to that from another recent large meta-analysis of 42 studies showing that use of a volatile anesthetic was associated with decreased one-year mortality compared with total intravenous anesthesia in patients undergoing cardiac surgery using cardiopulmonary bypass 2 . This apparent contradiction occurred despite fundamental similarities between the two meta-analyses: both studies followed strict PRISMA guidelines 3 ; both used the recommended Cochrane Risk of Bias Tool 4 ; both included most of the same original RCTs; and both designated one-year mortality as a primary outcome variable.…”
contrasting
confidence: 97%
“…The authors' analysis of 64 randomized controlled trials (RCTs) demonstrated that one-year mortality was similar between groups 1 . This conclusion stands in stark contrast to that from another recent large meta-analysis of 42 studies showing that use of a volatile anesthetic was associated with decreased one-year mortality compared with total intravenous anesthesia in patients undergoing cardiac surgery using cardiopulmonary bypass 2 . This apparent contradiction occurred despite fundamental similarities between the two meta-analyses: both studies followed strict PRISMA guidelines 3 ; both used the recommended Cochrane Risk of Bias Tool 4 ; both included most of the same original RCTs; and both designated one-year mortality as a primary outcome variable.…”
contrasting
confidence: 97%
“…In cardiac surgery, it has been well known that volatile, but not intravenous, anesthetics (propofol and midazolam) have cardioprotective effects [ 16 , 17 ]. When intravenous anesthetics are administered with volatile anesthetics, there may be interference with the cardioprotective effects of volatile anesthetics [ 18 ]. The cardioprotective effects of remimazolam and interactions between remimazolam and volatile anesthetics have not been elucidated.…”
Section: Discussionmentioning
confidence: 99%
“…Modes of application of the VA in these studies ranged from specific pre-or postconditioning protocols to administration of the VA during the entire surgical procedure. The most recent and largest meta-analysis, performed by Bonnani et al including 42 trials and 8197 patients, however, showed that VA are superior to propofol on long term mortality and postoperative morbidity [30]. In their analysis, the use of VA in patients undergoing cardiac surgery with the use of cardiac pulmonary bypass was associated with a lower one-year mortality, myocardial infarction, lower cTnT release, less need for inotropic support, shorter extubation time, and higher cardiac index/cardiac output compared to the use of propofol, indicating a myocardial protective effect of VA in this setting [30].…”
Section: Anesthetic Conditioning and Organ Protection With Volatile Anesthetic Agentsmentioning
confidence: 99%